Development of a Training Module for Process Operation based on Mixed-Reality Technology - Derya Kara (2024)
The aim of this master thesis is to create a training module with the use of mixed reality glasses in process engineering plant operation. The HoloLens 2 which is developed by Microsoft is utilized for this project, as well as 3D model of plant drawn in AutoCAD is transferred to Unity to design a training module which can be experienced in HoloLens 2 after the deployment in Visual Studio.